PENGARUH ORIENTASI STRATEGIS, KONTROL MANAJER PENJUALAN DAN KEANDALAN TENAGA PENJUALAN TERHADAP EFEKTIVITAS PENJUALAN MELALUI KINERJA TENAGA PENJUALAN (STUDI PADA PT. TELKOM WITEL SEMARANG) - Rizkia Putri, 13.05.51.0207; Rizal R, Alimuddin (Students Journal of Economic and Management, 2017)
This study aims to examine and analyze the influence of strategic orientation, sales manager control, and salesperson reliability on sales effectiveness through salesperson performance. This research was conducted at PT. TELKOM Witel Semarang which is one of state-owned companies.The sampling method used sampling saturated or census and the sample size as much as 90 respondents. The relationship or influence between variables is explained by using multiple regression analysis.The result of the research shows that strategic orientation has significant positive effect to salesperson performance. Sales manager control has a significant negative effect on salesperson performance. The reliability of sales force has a significant positive effect on salesperson performance and salesperson performance has a significant positive effect on sales effectiveness Keywords: Strategic Orientation, Sales Manager Control, Salesperson Reliability, Salesperson Performance, and Sales Effectiveness